2008
DOI: 10.1080/15459620802510866
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of Uses and Levels of Occupational Exposure to Tetrachloroethylene

Abstract: Tetrachloroethylene has been one of the most widely used chlorinated solvents in the United States. This review provides a basis for tetrachloroethylene exposure assessment in population-based case-control studies. We performed literature searches in MEDLINE, TOXLINE, NIOSHTIC, and the NIOSH Health Hazard Evaluation databases using relevant search terms. We calculated weighted arithmetic means from the measurement data and compiled these into three summary tables by type of operation: (1) dry cleaning, (2) deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 62 publications
2
46
0
1
Order By: Relevance
“…Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group [76,207] PBB Electronics recycling industry; maintenance/repair technicians of PBB devices [209][210][211][212] Group 2A [207] Chloral 75-87-6 Insecticides and herbicide production; p...…”
Section: Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maroni et al [105] reported the hepatotoxicity of VCM and other studies have shown the capacity of VCM to Group 1 [76] TCE 79-01-6 Dry cleaning; paint stripping; metal degreasing; production of chlorinated chemical compounds; shoe manufacturing; aircraft/aerospace, electronics and printing industry [125,127] Group 1 [129] PCE 127-18-4 Dry cleaning; textile processing; metal degreasing [138] Group 2A [129] DDT 50-29-3 Farming industry [141,145] Group 2B [148] N-nitrosamines 35576-91-1 Plastic, rubber and pharmacological manufacturing; farming industry; metalworking; electrical component production and use; gasoline and lubricant additives, production and use [159][160][161][162][163][164][165] Group [160,161] TCDD 1746-01-6 Waste management; paper mill; timber manufacturing; iron and steel manufacturing; electric power industry [175,179] Group 1 [76] PeCDF 57117-31-4 Cement and metalworking industry; chemical manufacturing [171,172,175] Group 1 [76] PCB 1336-36-3 Electrical industry, plastic and chemical industry; maintenance/repair technicians of PCB devices [175,[186][187][188][189][190] 1 Group [76,207] PBB Electronics recycling industry; maintenance/repair technicians of PBB devices [209][210][211][212] Group 2A [207] Chloral 75-87-6 Insecticides and herbicide production; p...…”
Section: Organic Solventsmentioning
confidence: 99%
“…A high prevalence of liver cancer was found in animal models exposed to PCE (CAS 127-18-4) [138,139] . Porru et al [140] showed that, in workers chronically exposed to organic solvents (toluene and xylene), there is an increased risk of HCC and that the risk is timedependent.…”
Section: -87-5mentioning
confidence: 99%
“…For instance, the material could be subjected to a drycleaning process, in which oils are essentially extracted with a solvent. However, in addition to the expense involved, there are also serious environmental concerns about the solvents employed (Altmann et al 1995;Delery et al 2008;Gold et al 2008). Thus, drycleaning would be hard to justify as a means to achieve environmental benefits.…”
Section: Regenerationmentioning
confidence: 99%
“…Databases of measurement levels across multiple industries have been constructed for some agents by abstracting data from the published industrial hygiene literature [e.g. solvents (van Wijngaarden and Stewart, 2003;Bakke et al, 2007;Gold et al, 2008)] or by utilizing existing databanks of exposure information [e.g. the Integrated Management and Information System (IMIS) database of air sampling data from US Occupational Safety and Health Administration inspections beginning in 1972].…”
Section: Discussionmentioning
confidence: 99%
“…Literature was identified from MEDLINE, TOXLINE, NIOSHTIC, and NIOSH HHE database searches, other reviews (e.g. Bakke et al, 2007;Gold et al, 2008), and personal archives. The compiled literature included primarily US journal articles and trade association reports , NIOSH HHEs (1976-1996, and NIOSH IWS reports [IWS reports prior to 1971 (the year NIOSH began) include reports from the US HEW/ HHS Bureau of Occupational Safety and Health.].…”
Section: Measurement Databasementioning
confidence: 99%